Response of benthic fauna to experimental bottom fishing: A global meta‐analysis. Issue 4 (2nd April 2018) - Sciberras, Marija; Hiddink, Jan Geert; Jennings, Simon; Szostek, Claire L; Hughes, Kathryn M; Kneafsey, Brian; Clarke, Leo J; Ellis, Nick; Rijnsdorp, Adriaan D; McConnaughey, Robert A; Hilborn, Ray; Collie, Jeremy S; et al.
Abstract: Bottom‐contact fishing gears are globally the most widespread anthropogenic sources of direct disturbance to the seabed and associated biota. Managing these fishing disturbances requires quantification of gear impacts on biota and the rate of recovery following disturbance. We undertook a systematic review and meta‐analysis of 122 experiments on the effects‐of‐bottom fishing to quantify the removal of benthos in the path of the fishing gear and to estimate rates of recovery following disturbance. A gear pass reduced benthic invertebrate abundance by 26% and species richness by 19%. The effect was strongly gear‐specific, with gears that penetrate deeper into the sediment having a significantly larger impact than those that penetrate less. Sediment composition (% mud and presence of biogenic habitat) and the history of fishing disturbance prior to an experimental fishing event were also important predictors of depletion, with communities in areas that were not previously fished, predominantly muddy or biogenic habitats being more strongly affected by fishing. Sessile and low mobility biota with longer life‐spans such as sponges, soft corals and bivalves took much longer to recover after fishing (>3 year) than mobile biota with shorter life‐spans such as polychaetes and malacostracans (<1 year). This meta‐analysis provides insights into the dynamics of recovery. Our estimates of depletion along with estimates of recovery rates and large‐scale, high‐resolution maps of fishing frequency and habitat will support more rigorous assessment of the environmental impacts of bottom‐contact gears, thus supporting better informed choices in trade‐offs between environmental impacts and fish production.